Simple Photo-Induced Trifluoromethylation of Aromatic Rings - Egami, Hiromichi; Ito, Yuta; Ide, Takafumi; Masuda, Shuya; Hamashima, Yoshitaka (Synthesis, 2018)
The trifluoromethylation of various aromatic compounds with Umemoto reagent II (2,8-difluoro-5-(trifluoromethyl)-5H-dibenzo[b,d]thiophen-5-ium triflate) proceeded in moderate to good yields under simple photo-irradiation conditions without any catalyst, additive, or activator. UV-Vis and NMR spectral analyses indicated that pre-formation of an electron donor-acceptor complex between the trifluoromethylating reagent and the substrate, as proposed in previous studies, is not essential for generation of the trifluoromethyl radical. Instead, the radical appears to be formed by simple photo-activation of the Umemoto reagent.
Keywords: trifluoromethylation; radical; photo-irradiation; Umemoto reagent; aromatic substitution